Modelling of Bearing Lubrication for Electric Vehicle Motor Bearing - Siti Hartini, Hamdan; Lee, Chiew Tin; Hao, Ng Jian (Penerbit UTM Press, 2025)
Bearing failure in electric motors is increasingly attributed to complex electro-thermal interactions that accelerate surface damage and lubricant degradation. Electrical current discharge disrupts the lubricant’s rheological properties, diminishing film thickness and undermining protection in the elastohydrodynamic lubrication regime. This study presents a numerical model that integrates EHL theory with heat generation from shear and electrical sources while capturing the influence of key operating parameters such as shaft speed, bearing resistivity, and temperature. The findings reveal that current discharge markedly reduces minimum film thickness and distorts pressure distribution due to localised temperature rise and viscosity breakdown. The model demonstrates strong predictive capability by capturing the coupled effects of entrainment, rheological degradation, and electro-thermal loading. These results underscore the sensitivity of EHL film formation to electrical stress and highlight potential failure thresholds under realistic operating conditions. The insights gained can inform the development of advanced bearing systems with enhanced thermal management, electrical insulation, and lubricant formulation strategies, ultimately improving the durability and reliability of electric motor drivetrains.